A Concise introduction to data structures using Java - Johnson, Mark J. (Boca Raton, Florida : CRC Press, 2014)
A student-friendly text, A Concise Introduction to Data Structures Using Java takes a developmental approach, starting with simpler concepts first and then building toward greater complexity. Important topics, such as linked lists, are introduced gradually and revisited with increasing depth. More code and guidance are provided at the beginning, allowing students time to adapt to Java while also beginning to learn data structures. As students develop fluency in Java, less code is provided and more algorithms are outlined in pseudocode. The text is designed to support a second course in computer science with an emphasis on elementary data structures. The clear, concise explanations encourage students to read and engage with the material, while partial implementations of most data structures give instructors the flexibility to develop some methods as examples and assign others as exercises. The book also supplies an introductory chapter on Java basics that allows students who are unfamiliar with Java to quickly get up to speed. The book helps students become familiar with how to use, design, implement, and analyze data structures, an important step on the path to becoming skilled software developers.
1. A brief introduction to Java -- 2. Algorithm analysis -- 3. Integer stacks -- 4. Generic stacks -- 5.Queues -- 6. Lists -- 7. Recursion -- 8. Trees -- 9. Binary search trees -- 10. Heaps -- 11. Hash tables.
Includes bibliographical references and index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)